A review on recent advances in dry reforming of methane over Ni- and Co-based nanocatalysts - Sharifianjazi, F. (Elsevier Ltd, 2021)
The recent environmental-related issues such as climate change and global warming have sparked scientists' interest in finding a way to reduce the emission of greenhouse gases through dry reforming of CH4. As a result of this reaction, not only H2 is produced, but also CO2 and CH4 are reduced. Catalysts are needed due to the enhancement of the kinetics of the reaction. Non-noble metals like Ni, Co, etc., have shown promising activity, they are readily available, and have low cost; consequently, they have been widely employed for the reaction. In this paper, the recent advances in the development of the Ni- and Co-based nanocatalysts for DRM reaction, including the use of different supports and promoters, the addition of alkaline earth metals, and new structures like mesoporous silica and dendritic fibrous nano silica as supports were reviewed. Â© 2021